2010
DOI: 10.1080/01425690903385451
|View full text |Cite
|
Sign up to set email alerts
|

‘Go, go on and go higher an’ higher’. Second‐generation Turks’ understanding of the role of education and their struggle through the Dutch school system

Abstract: With reference to capital theories and rational choice theory, this paper aims to understand how abilities and schooling ambitions are intertwined with social class, gender and ethnicity. By drawing on 16 in-depth interviews carried out with highly educated second-generation Turks in the Netherlands, the paper discusses the resources, opportunities and educational attitudes of young people, together with the role of the school system and that of teachers in perpetuating ethnic inequalities in schooling, with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 14 publications
1
25
0
2
Order By: Relevance
“…In the Netherlands when guest worker migrants abandoned their return plan to their country of origin and started to become aware of the relevance of educational credentials for achieving upward social mobility, they adjusted their ambitions for their children accordingly. Young marriages and long school routes made room for making full use of the Dutch opportunity structures, such as educational opportunities (Coenen, 2001;Crul, 2009;Pásztor, 2010). As scholars studying aspirations and optimism of immigrant parents in the US have addressed (See Kao and Tienda, 1995;Louie, 2012;Portes and Fernández Kelly, 2008;Raleigh and Kao, 2010;Smith, 2008), Dutch academics have observed that being supported morally and emotionally by parents has a positive influence on the educational achievements of the second generation of Turkish and Moroccan origin (Crul and Schneider, 2010;Nanhoe, 2012;Pásztor, 2010).…”
Section: Second Generation and Supportmentioning
confidence: 99%
“…In the Netherlands when guest worker migrants abandoned their return plan to their country of origin and started to become aware of the relevance of educational credentials for achieving upward social mobility, they adjusted their ambitions for their children accordingly. Young marriages and long school routes made room for making full use of the Dutch opportunity structures, such as educational opportunities (Coenen, 2001;Crul, 2009;Pásztor, 2010). As scholars studying aspirations and optimism of immigrant parents in the US have addressed (See Kao and Tienda, 1995;Louie, 2012;Portes and Fernández Kelly, 2008;Raleigh and Kao, 2010;Smith, 2008), Dutch academics have observed that being supported morally and emotionally by parents has a positive influence on the educational achievements of the second generation of Turkish and Moroccan origin (Crul and Schneider, 2010;Nanhoe, 2012;Pásztor, 2010).…”
Section: Second Generation and Supportmentioning
confidence: 99%
“…Ethnic minorities are often at a disadvantage in these highly stratified school systems. Being channelled into low or dead-end tracks early on makes it extremely difficult, if not impossible, for them to reach access to higher education later on (Pasztor, 2010). Transition from VMBO to MBO is particularly problematic, as many failed to make such transition and dropout of the education system (Elffers, 2012).…”
Section: The Organization Of Schooling and Transitionsmentioning
confidence: 99%
“…Since ethnic minority students are generally channelled to the least selective secondary school tracks (Pásztor 2010) such 'indirect access' is often the only way they can access HE at all. As a result, professional colleges tend to have a relatively high proportion of ethnic minority student population while universities only a very small.…”
Section: Access To Higher Education In the Netherlandsmentioning
confidence: 99%
“…Hence, a very low level of parental education (often limited to primary schooling), lack of knowledge of the Dutch language and of the Dutch labour market, characterised the first generation. But gradually, education became to be seen as a way of achieving social mobility and providing improved life chances for the next generations who were to make their futures in Dutch society (Heath et al 2008;Pásztor 2010). …”
Section: Introductionmentioning
confidence: 99%